Implementasi Terapi Slow Stroke Back Massage (SSBM) untuk Meningkatkan Kualitas Tidur pada Klien Post Op Sectio Caesarea - Mardiana Mardiana; Irawati Irawati; Muhammad Basri (Jurnal Anestesi, 2025)
According to WHO (2015), health research results increase births with Sectio Caesarea in all countries around 50-150 per 1,000 births in the world. Post-operative conditions can cause physical discomfort in patients, such as nausea, vomiting and pain. The pain felt by an individual is a stimulus that affects sleep quality. One of the non-pharmacological therapies to overcome postpartum Sectio Caesarea maternal sleep pattern disorders is Slow Stroke Back Massage therapy. This therapy is an effective therapy for treating sleep pattern disorders and can increase comfort with sensory integrity techniques that affect the autonomic nervous system.Objective: To provide nursing care to clients who experience problems with sleep patterns due to post op caesarean section by providing slow stroke back massage therapy at the Hapsah Hospital, Bone Regency.Method: This research is qualitative research using the case study method. The data collection techniques are through interviews, questionnaire methods, measurement and observation.Results: After providing nursing care to clients who experienced sleep pattern disturbances due to post op caesarean section with the provision of slow stroke back massage therapy intervention from the three respondents, there was one respondent who stated that the problem of sleep pattern disturbances had not been resolved. This is due to several factors, namely complaints of pain, fussy babies, changes in sleep patterns in the final trimester of pregnancy and the provision of therapy on the second day of implementation not in accordance with the SOP with a time of 8 minutes.Conclusion: After providing nursing care for 3 days, it can be concluded that the slow stroke back massage therapy nursing action is effective for clients who experience sleep disturbances due to post op caesarean section.